Tree-stem diameter fluctuates with the lunar tides and perhaps with geomagnetic activity - Barlow, Peter W; Mikulecký, Miroslav Sr; Střeštík, Jaroslav (Protoplasma, 2010)
Our initial objective has been to examine the suggestion of Zürcher et al. (Nature 392:665-666, 1998) that the naturally occurring variations in stem diameter of two experimental trees of Picea alba were related to near-simultaneous variations in the lunisolar tidal acceleration. The relationship was positive: Lunar peaks were roughly synchronous with stem diameter peaks. To extend the investigation of this putative relationship, additional data on stem diameter variations from six other tree species were gathered from published literature. Sixteen sets of data were analysed retrospectively using graphical representations as well as cosinor analysis, statistical cross-correlation and cross-spectral analysis, together with estimated values of the lunisolar tidal acceleration corresponding to the sites, dates and times of collection of the biological data. Positive relationships were revealed between the daily variations of stem diameter and the variations of the lunisolar tidal acceleration. Although this relationship could be mediated by a 24.8-h lunar rhythm, the presence of a solar rhythm of 24.0 h could not be ruled out. Studies of transpiration in two of the observed trees indicated that although this variable was not linked to stem diameter variation, it might also be subject to lunisolar gravitational regulation. In three cases, the geomagnetic Thule index showed a weak but reciprocal relationship with stem diameter variation, as well as a positive relationship with the lunisolar tidal force. In conclusion, it seems that lunar gravity alone could influence stem diameter variation and that, under certain circumstances, additional regulation may come from the geomagnetic flux.